Participatory development of educational technology in seeking patient safety in maternity hospitals - Manuela Estrela Baggio; Anna Caroline Leite Costa; Leyla Gabriela Verner Amaral Brandão; Vivian Andrezza Alves Andrade; Fernanda Penido Matozinhos; Allana dos Reis Corrêa; Bruna Figueiredo Manzo (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to develop a booklet as an educational technology, together with health professionals, patients and companions, aiming at their involvement in patient safety in maternity hospitals. Methods: a qualitative convergent care study, carried out in three stages at a maternity hospital in Belo Horizonte. The booklet construction took place between February and April 2021, with 13 professionals, 06 companions and 11 patients. Results: data content analysis was performed, creating three categories: Knowledge and experiences about patient and newborn safety in maternity hospitals; Challenges for involving patient and companion in safety actions; Assessment of patients, companions and professionals on the booklet construction process. The booklet construction involved the participation of health professionals, users and companions in all stages of the process. Final considerations: the participatory process enabled the creation of educational technology for the involvement of patients and companions in patient safety actions.